1978
DOI: 10.1002/qua.560140411
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence, complex scaling, and the calculation of resonances in many‐electron systems

Abstract: The theory of this paper deals with certain aspects of the formal properties of atomic and molecular highly excited nonstationary states and the problem of calculating their wave functions, energies, and widths. The conceptual framework is a decay theory based on the consistent definition and calculation of the t = 0 localized state, |Ψ. Given this framework, the following topics are treated: (a) The variational calculation of Ψ0 and E0 using a previously published theory that generalized the projection operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
120
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 89 publications
5
120
0
Order By: Relevance
“…Using Sturmian functions, the properties of the resonances can be calculated directly using the complex rotation technique [119][120][121][122][123][124][125]. The price to pay is to diagonalize complex symmetric matrices, instead of real symmetric ones.…”
Section: Hamiltonian Basis Sets and Selection Rulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Sturmian functions, the properties of the resonances can be calculated directly using the complex rotation technique [119][120][121][122][123][124][125]. The price to pay is to diagonalize complex symmetric matrices, instead of real symmetric ones.…”
Section: Hamiltonian Basis Sets and Selection Rulesmentioning
confidence: 99%
“…By inserting equations (121,122) in eq. (164), after appropriate account for the projection of the body-fixed frame (x ′ , y ′ , z ′ ) onto the laboratory frame (x, y, z), eq.…”
Section: Resonance Analysismentioning
confidence: 99%
“…Moreover, for long times, Nicolaides work [4,5] predicts non-exponential decay to be an inverse power law proportional to t −2 . Again, later work has shown that this long-time non-exponential decay is actually proportional to t −3/2 [2].…”
Section: G(t) Ln[−(i/h)z 0 T]mentioning
confidence: 99%
“…In his earlier work, he also derived the expression for P (t) given by equation (1) in his Comment which he claims holds for all t. Numerical evaluation of this function as shown in [4,5] does indeed show an exponential region followed by non-exponential decay after many lifetimes for large R (= E r /Γ).…”
mentioning
confidence: 99%
See 1 more Smart Citation